Legal Protection for Participants Regarding the Minutes of The Deed as Part of The Notary Protocol Which Was Destroyed Due To Fire - Fauziah Rachmadyta; Mahendra Wardhana (Universitas Negeri Surabaya, 2025)
The purpose of this study is to analyze the legal protection for the Parties against the Deed Minute as part of the Notary Protocol that was destroyed by fire and efforts to obtain a copy of the Deed as an interest for the Confronters after the Deed Minute was destroyed by fire. The research method used is normative research using a research approach in the form of a statutory approach using Article 28D paragraph (1) of the 1945 Constitution, Article 1889 paragraph (1) and paragraph (2) of the Civil Code, and Article 16 paragraph (1) letter b of the UUJN-P constructed by the method of legal discovery, namely Argumentum per analogiam and using a concept approach. The result of the research is that there is no regulation related to legal protection for the Parties if the Minute of Deed is damaged or destroyed due to fire or force majeure. Furthermore, regarding efforts to obtain a second or subsequent copy of the Deed for the Faces after the destruction of the Deed Minute due to fire.